Building Extraction With Morphology - Acar, Ugur; Bayram, Buelent (IEEE, 2009)
Building extraction is one of the biggest problems of the photogrammetry. Automatic building extraction from aerial imagery in an urban environment is the main focus of this study. The strategy of our approach is to reduce the complexity of the image with the mathematical morphology. True color aerial images have been used as the information source. In this study, the mathematical morphologic operator has been used to close and eliminate the unwanted objects over the building roofs. The successes of this method are about the elimination of the unwanted objects and keep up the structure of the building. Because of different style of urbanization, four different location and six high resolution ikonos satellite image have been used. The results are %85 of success.
Keywords: morphology; building extraction; image proccessing; MATHEMATICAL MORPHOLOGY; Engineering